Synthesis and biological evaluation of 2-arylbenzimidazoles targeting Leishmania donovani. Issue 9 (1st May 2015) - Keurulainen, Leena; Siiskonen, Antti; Nasereddin, Abedelmajeed; Kopelyanskiy, Dmitry; Sacerdoti-Sierra, Nina; Leino, Teppo O.; Tammela, Päivi; Yli-Kauhaluoma, Jari; Jaffe, Charles L.; Kiuru, Paula
Graphical abstract